PARTISIPASI POLITIK MASYARAKAT PADA PEMILIHAN UMUM LEGISLATIF TAHUN 2019 - Abdussyakur Abdussyakur; Okianna Okianna; Bambang Budi Utomo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aims to analyze the political participation of the society in Peniraman Village, Sungai Pinyuh District, Mempawah Regency. This research is a qualitative descriptive study. The focus of this research is to describe the factors that influence the high level of society political participation in Peniraman Village, Sungai Pinyuh District, Mempawah Regency. The object of this research is the society in Peniraman Village, Sungai Pinyuh District, Mempawah Regency, who use their voting rights in the 2019 legislative elections. Data collection techniques were done by interview and documentation methods. The data obtained were analyzed using an interactive model. The results show that the factors that influence the high political participation of the people of Peniraman Village, Sungai Pinyuh District in using their voting rights are influenced by political awareness factors which can be seen from the awareness of society rights and obligations in general training, fairly good society political knowledge and interest in society attention to voting. Another factor is public trust in the government, both support for government performance and public trust. And social factors, education, and heredity. Keywords: Legislative, Society, Political Participation.